Sequential batch thermophilic solid-state anaerobic digestion of lignocellulosic biomass via recirculating digestate as inoculum – Part II: Microbial diversity and succession. (October 2017) - Lin, Long; Yu, Zhongtang; Li, Yebo
Highlights: Effect of recirculating digestate as inoculum on microbial communities was studied. Microbes shifted toward stable state with increased diversity in the first 3 runs. Relative abundance of Firmicutes increased from 40% to 80% from run 1 to run 3. Methanothermobacter was enriched at volatile fatty acid (VFA) levels of 6–14 g/kg. Proportions of archaea rose from 1% to 5% from run 1 to run 4 when methane peaked. Abstract: This study aimed to investigate the effect of recirculation of digestate as inoculum on the microbial communities in thermophilic solid-state anaerobic digestion (SS-AD) of yard trimmings. The SS-AD consisted of 4 consecutive runs (30 days/run), with digestate from the previous run being used as the inoculum of the subsequent run. Bacterial and archaeal communities (day 0, 4, 8, 12, 20, and 30) were examined using Illumina sequencing of 16S rRNA genes. The results revealed substantial microbial succession toward increased diversity until run 3. The proportions of Firmicutes that contained cellulolytic bacteria doubled, which might explain the concomitantly increased cellulose degradation and volatile fatty acids (VFAs). Clostridia and Thermotogae appeared to correlate with VFAs. The VFA accumulation likely induced dynamic shifts of methanogens, particularly to hydrogenotrophic Methanothermobacter, implying that non-acetoclastic oxidative pathway dominated during the steady-state thermophilic SS-AD. This study suggested that recirculating SS-AD digestate might be an effective way for inoculation.